Heterogeneous photocatalytic cyanomethylarylation of alkenes with acetonitrile: synthesis of diverse nitrogenous heterocyclic compounds - Pan, Guanglong; Yang, Qian; Wang, Wentao; Tang, Yurong; Cai, Yunfei (Beilstein Journal of Organic Chemistry, 2021)
A visible light-mediated heterogeneous photocatalytic cyanomethylarylation of alkenes with acetonitrile has been established using K-modified carbon nitride (CN-K) as a recyclable semiconductor photocatalyst. This protocol, employing readily accessible alkyl N-hydroxyphthalimide (NHPI) ester as a radical initiator, allows the efficient construction of a broad array of structural diverse nitrogenous heterocyclic compounds including indolines, oxindoles, isoquinolinones, and isoquinolinediones.
Keywords: carbon nitride; cyanoalkylarylation; heterocyclic compound; heterogeneous photocatalysis; recyclable